(untitled) (Global Journal of Human-Social Science, 2023)
This personal account of my encounters with reading and writing in my professional development as mathematics teacher invites the reader to think about the possibilities of connecting with different forms of language manifestation This article reviews concepts of free writing and the expressive and transactional functions of writing It reflects on alternatives and instruments that can enhance different means of report including communication in computer environments The deep-reading construct introduces the importance of hyperconnected registers This hyperconnection involves creative production via networked digital technologies and does not consider writing as the form of most outstanding cognitive value or centrality